UPAYA PENINGKATAN KOMPETENSI STAF TATA USAHA DALAM MENGELOLA ADMINISTRASI KEPEGAWAIAN MELALAUI PENDAMPINGAN DI SMA NEGERI SUNGAI BEREMAS - Puardi, Puardi (Jurnal Manajemen Pendidikan, 2018)
Administrative staff (TU) has an important role in helping to develop the school become more advanced and qualified. The school administrative force serves as a school administration administrator associated with the management of student data, educator data and education personnel, mailing, archives, administration of facilities, and financial administration. TAS also plays an active role in providing administrative services to all interested parties. Therefore it is necessary to improve the competence of administrative staff. The type of research used is action research, ie the researcher attempted to apply an action as an improvement effort to overcome the problems found. Because the research is conducted with class setting, it is called Classroom Action Research This classroom action research is SMA Negeri 1 Susngai Beremas, Kabupaaten Pasaman Barat.In this classroom action research using two data analysis techniques taking into account the type of data collected, namely qualitative analysis and quantitative analysis Qualitative analysis of qualitative data obtained from the results of the instrument pengisina in accordance with the dat in the school.Based on the frame of thought and the results of implementation of leadership actions carried out by two cycles then made conclusions, the level of competence of the school administration determine the success of schools in achieving the established goals.Competency of school administrative staff in managing personnel administration can be improved through the guidance by the principal in his capacity as a manager at school.